Circulating hybrid cells predict presence of occult nodal metastases in oral cavity carcinoma. Issue 7 (9th April 2021) - Henn, Tara E.; Anderson, Ashley N.; Hollett, Yvette R.; Sutton, Thomas L.; Walker, Brett S.; Swain, John R.; Sauer, David A.; Clayburgh, Daniel R.; Wong, Melissa H.
Abstract: Background: Levels of circulating hybrid cells (CHCs), a newly identified circulating tumor cell (CTC), correlate with disease stage and progression in cancer. We investigated their utility to risk‐stratify patients with clinically N0 (cN0) oral cavity squamous cell carcinoma (OCSCC), and to identify patients with occult cervical lymph node metastases (pN+). Methods: We analyzed peripheral blood samples for CHCs with co‐expression of cytokeratin (tumor) and CD45 (leukocyte) from 22 patients with cN0 OCSCC using immunofluorescence microscopy, then correlated levels with pathologic lymph node status. Results: CHC levels exceeded CTCs and correlated with the presence of both clinically overt ( p = 0.002) and occult nodal metastases ( p = 0.006). Conclusions: For evaluated cN0 OCSCC patients, those with cN0 → pN+ status harbored elevated CHC levels compared to patients without occult disease. Our findings highlight a promising blood‐based biologic assay with potential utility to determine the necessity of surgical neck dissection for staging and treatment.